FAKTOR-FAKTOR YANG MEMPENGARUHI MENURUNNYA USIA KAWIN PERTAMA DI PROVINSI BALI - I Ketut, Sudibia; I G A, Manuati Dewi; I Nyoman, Dayuh Rimbawan (PIRAMIDA, 2015)
This research aimed to explore the factors that influence the age at first marriage of women in Bali. It is important and urgent to carry out given the results of Indonesia Demographic Health Survey of 2007 and 2012 that showed an increase in the total fertility rate of Bali’s population from 2.1 to 2.3 per woman of reproductive age during the 2007-2012 period. Even the more crucial thing was the increase in the fertility rate that in fact occurred in the younger age group (15-19), which was from 18 to 48 per 1000 women during the period of 2007-2012. This condition indicates that lately early marriage tended to increase. This research was conducted in three areas, namely Bangli, Gianyar and Denpasar. The selection of these three regions is based on the structure of the economy, with the following details: (1) Bangli represents a region with the economic structure that largely oriented towards Primary Sectors, (2) Gianyar represents a region with nearly balanced economic structure between Primary and Non-Primary Sectors and (3 ) Denpasar represents the area with economic structure of Tertiary Sectors (services). In each region, it was selected four villages (except in Denpasar that was for five villages), and the selection of villages was done randomly. Furthermore, of all selected villages, itwas chosen as many as 600 respondents randomly. Respondents were the wifes of the couples who got married within the last five years (2009-2013). The data collection was conducted by using structured interviews, and data analysis technique used was multiple linear regression. Important conclusions obtained from the research were (1) the respondents’ education, access to mass media, the value of assets of the parents, and the working status, respectively had a positive effect on the age at first marriage; (2) the number of family members, the habit of parents encourage their children to get married at the younger age, and the better treatment of parents of boys than girls would negatively affect the age at first marriage (3) the knowledge about early marriage did not affect the age at first marriage; and (4) the respondents who were married because of “MBA” (married by accident), their first age of marriage were younger than those who got married not because of “MBA”. Furthermore, based on the above findings, it can be suggested the following recommendations (1) the improvement education for women; (2) poverty alleviation; (3) the expansion of employment opportunities for women; and (4) BKKBN as the Family Planning Coordinating Agency which have already introduced a program of GenRe / Generation Planning in several educational institutions and religious organizations needs to be enhanced the coverage and increased the intensity of the activities.
Keywords: the age at first marriage; women’s education; working status